Synthesis and pH‐Dependent Spectroscopic Behavior of 2, 4, 6‐Trisubstituted Pyridine Derivatives. (11th June 2014) - Chapman, Gala; Solomon, Isaac; Patonay, Gabor; Henary, Maged
<x xml:space="preserve">Abstract</x> Seven 2, 4, 6‐trisubstituted pyridine derivatives with N, N‐diethylaniline substituents at the 4‐position were synthesized, and their spectroscopic properties in the absence and presence of acid were studied. The spectral effects of protonation, molar absorptivities, pKa values, and the structural origins of the observed spectral behavior were ascertained. The pyridine nitrogen was found to be more basic than the diethylamino nitrogen atom. Protonation of the pyridine ring nitrogen is associated with the appearance of a red‐shifted intramolecularcharge transfer peak in the UV‐visible spectra. Favorable color indicating properties result from electron‐donating substitution at the 2 and 6 positions of pyridine, which provide a greater absorptivity of the red‐shifted peak associated with protonation of the pyridine nitrogen. These findings will assist in the design and optimization of these compounds for ion‐indicating and pH‐sensing applications.